Study on Hybrid Fuzzy Controller Design by Model Reduction Method - Ho Cho, Joon; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: The combustion of fossil fuels and increased number of advanced technology leads to the global warming and climate change. So, to reduce the greenhouse gas emission and conserve the energy we need to use green energy like fuel cell and Li-ion battery system. This hybrid system consists of PEM fuel cell stack, Li-ion battery and bidirectional step up converter and can be used stationary as well as mobile equipment like vehicles. Methods/Statistical analysis: For the analysis of hybrid PEMFC/ Li-ion battery power supply system, portable embedded motor is proposed in this paper. The modeling, design, implementation and performance of hybrid system are demonstrate by using experimental results as well as MATLAB/Simulink. Findings: The simulation results shows that hybrid fuel cell-battery system could provide the continuous power to the sudden changing load and protect the devices. The results also shows that, bidirectional controller can successfully control the fuel cell output and maintain the state of charge of battery at a constant level which provides the significant efficiency of the hybrid power supply system and increased the life-cycle of the system more than 35%. Improvements/Applications: To improve the fuel cell system performance we need to provide the favorable conditions of temperature, pressure, humidity and control the flow rate of reactant gausses. Similarly, due to internal resistance, temperature, material used in manufacturing process, charging and discharging strategy reduces the efficiency as well as life of the battery pack. By using proper voltage balancing methodology we can maintain the similar voltage and prevent from irregular charging.